Seni Ukir Kayu Khas Palembang di Home Industri Q Laquer Kota Palembang - Mainur Mainur (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
This article is the result of a typical Palembang wood carving work. Starting from the increasingly few antiques in the antique gallery owned by Ibu Hj's family. Roswati made him intrigued to grow and develop his business since 1974 and to preserve the carving art furniture in the form of Palembang wood carving. Then continued by a similar craftsman in the Home Industry Q Laquer owned by Mr. Jaja is a typical Palembang wood carving art craftsmanship in Kelurahan 19 Ilir. The purpose of this research is to find out and describe the process of making Palembang's unique wood carving arts. The research method used is a qualitative descriptive method using data collection techniques of observation, interviews, and documentation. The types of decoration in the wood carving art are the decoration that characterizes the city of Palembang as from the motifs of plants with golden, black, and red patterns. The variety of wood carving that is applied to handicraft objects is basically a pure decoration, which functions solely to decorate or beautify. The results of typical Palembang carving crafts include decorative cabinets, chairs, tables, wardrobes, frames, and various kinds of furniture. Through this research by examining how Palembang wood carving art in particular the manufacturing process, is expected to contribute to the people of Palembang City in order to develop and preserve these cultural assets.